Investigation of the Effect of Boron Oxide and Beeswax on Workability and High-Temperature Performance of Bitumen - Sahan, Neslihan; Oruc, Seref; Cavdar, Erman; Kumandas, Aytug; Kabadayi, Ersoy; Kok, Baha Vural (Springer Heidelberg, 2025)
In recent years, various studies have shown that boron-containing additives improve the rutting performance of the bituminous pavements. However, in these studies, it was stated that these additives would decrease the workability of the bitumen and increase energy required for the construction of the pavement. On the other hand, it has been shown in many studies that waxes increase the workability of the bitumen. In this study, it was aimed to obtain bitumen with high rutting resistance and workability by adding boron oxide (BO) and beeswax (BW) to bitumen. Therefore, modified bitumen was produced by adding BO and BW at different ratios to a 50/70 penetration grade base bitumen. Then, the chemical, physical, and rheological properties of modified bitumen samples were investigated by various experiments. As a result, it has been observed that BO increases the high-temperature performance and viscosity of bitumen; on the other hand, BW decreases rutting resistance and viscosity. When BO and BW were added together to the bitumen, the negative impact of BO on workability and the negative impact of BW on high temperature performance were significantly eliminated. Especially, in 1BO + 1BW and 3BO + 3BW bitumens, the high-temperature performance of the bitumen improved without decreasing the workability.
Keywords: Bitumen modification; Boron oxide; Beeswax; Wax; Workability; Rutting